Rahova Uranus: un cartier dormitor? - Voicu, Bogdan; Nițulescu, Dana Cornelia (Calitatea Vieții, 2007)
The paper focuses on the youth from the Rahova – Uranus area, in Bucharest. Using qualitative data, we deal with the representations about the main needs of the neighborhood, we explore the cultural practices and the representations about the cultural practices. We show out that the basic needs of personal security, housing, and a clean neighborhood prevail any quality of life component. The low level of cultural practice in the area, as well as the wide-spread rejection of the area as a place for social and cultural life, determines the two authors to label it as a dormitory-neighborhood. Several explanations are given, in a paper that has mainly a documentary contribution to the knowledge of the current processes in Bucharest.